Centenary of the Natal Herbarium, Durban, 1882-1982 - B. D. Shrire (Bothalia: African Biodiversity & Conservation, 1983)
The history of the Natal Herbarium is described from its inception in 1882 to 1982, the year of its centenary. Its history is inextricably linked with that of the Durban Botanic Gardens which started as an Agricultural Garden in 1848, and the Durban Botanic Station. The roles played by various curators and officers-in-charge, especially John Medley Wood, who held office for 32 years and did much to put the Herbarium on the botanical map, are emphasized.